2019
DOI: 10.1016/j.jad.2018.11.077
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep fragmentation associated with depressive symptoms and genetic risk for depression in a community-based sample of adolescents

Abstract: , REM sleep fragmentation associated with depressive symptoms and genetic risk for depression in a community-based sample of adolescents,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…However, we found that on school days most adolescents do not sleep eight hours, these results are in concordance with surveys from different countries 29,32 . Sleep deprivation increases with age 41 , although the importance that this finding may have for adolescents is still being discussed 31,42,43 . In our sample, low levels of parental education and emotional instability were associated with higher prevalence of sleep problems in adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that on school days most adolescents do not sleep eight hours, these results are in concordance with surveys from different countries 29,32 . Sleep deprivation increases with age 41 , although the importance that this finding may have for adolescents is still being discussed 31,42,43 . In our sample, low levels of parental education and emotional instability were associated with higher prevalence of sleep problems in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who are sleep deprived have greater intolerance to stress, emotional dysregulation, behavioural disorders, depression, and other emotional disorders [29][30][31] . Different longitudinal studies have indicated that lack of sleep, emotional dysregulation, and depressive symptoms interact with each other simultaneously as causes and consequences 29,30 .…”
mentioning
confidence: 99%
“…Increasing autonomy and early school start time predispose adolescents to shortened sleep duration and sleep problems, such as sleep fragmentation, especially on school days (Lehto et al 2016). As a result, this can increase daytime tiredness, depressive symptoms, and burnout, leading to poor daytime functioning (Pesonen et al 2019). Teenage years are also characterized by a circadian shift to eveningness (Roenneberg et al 2007), with a biological tendency towards later bedtime and the need to compensate this with a later wake-up time.…”
Section: Sleep Functioning In Adolescencementioning
confidence: 99%
“…From research in depressive participants, an earlier onset of REM sleep and more REM sleep has been associated with stronger depressive symptoms, and a reduction in REM sleep has been suspected to be beneficial for treatment outcomes. [50][51][52][53][54] However, whether less REM sleep is beneficial for emotional regulation in healthy participants is not clear. As participants were also not instructed to manipulate REM sleep, the reason and impact of the reduction of REM sleep after the instruction to sleep "good" remains elusive but may be interpreted as an impairment of sleep.…”
Section: Discussionmentioning
confidence: 99%